Boosting Informatics Interest with Google Classroom: A Study on 10th Graders at State Senior High School 8 Malang - Anwar, Akhmad Syaiful; Fatmawati, Hefi; Ramadiani, Nanda Resta; Hikmah, Nur; Hidayat, Manik; Mubarok, Sulton (Universitas Negeri Malang, 2024)
In the learning process, an educator can choose and use several strategies, methods and learning media appropriate to the subject matter and the character of the students being taught. This research aims to determine how students' interest in learning is taught using Google Classroom media in the Informatics subject. This research is experimental. The subjects of this research were class X students of SMA Negeri 8 Malang. Meanwhile, the number of samples that will be used in this research is 42 respondents. The instrument used in this research is a questionnaire, and the type of data analysis used is quantitative. It is hoped that the results of this research can contribute to the use of Google Classroom media in the future as input, suggestions, or considerations in developing learning strategies